Professional development on a budget: facilitating learning opportunities for information literacy instructors - Shamchuk, Lisa (My University, 2015)
How do you stay on top of evolving trends and changes to information literacy delivery, especially while coping with shrinking professional development allocations? This article details various in-house, professional development opportunities created for MacEwan University’s library staff. Low-cost, practical ideas are given to help jump-start a library's information literacy professional development offerings. Included are details about organizing an Information Literacy Community, internal Library Professional Development Days and an information literacy event open to local library professionals.
Keywords: professional development; information literacy; conference planning